2022
DOI: 10.1182/bloodadvances.2022007099
|View full text |Cite
|
Sign up to set email alerts
|

Temporal in vivo platelet labeling in mice reveals age-dependent receptor expression and conservation of specific mRNAs

Abstract: The proportion of young platelets, also known as newly formed or reticulated, within the overall platelet population has been clinically correlated with adverse cardiovascular outcomes. Our understanding of this is incomplete, however, because of limitations in the technical approaches available to study platelets of different ages. In this study we have developed and validated an in vivo 'temporal labelling' approach using injectable fluorescent anti-platelet antibodies to sub-divide platelets by age and asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 49 publications
5
19
0
Order By: Relevance
“…Studies using murine platelets have shown that young platelets have higher levels of MHC-I and PECAM-1. 41,61 Consistent with these murine studies, young thiazole orange bright human platelets express higher levels of surface HLA-I and have higher ribosomal contents than older platelets. Indeed, the authors of this study suggest that HLA-I may be a better marker than thiazole orange to determine the percentage of young platelets in patient samples.…”
Section: Surface Receptor Contentsupporting
confidence: 65%
See 4 more Smart Citations
“…Studies using murine platelets have shown that young platelets have higher levels of MHC-I and PECAM-1. 41,61 Consistent with these murine studies, young thiazole orange bright human platelets express higher levels of surface HLA-I and have higher ribosomal contents than older platelets. Indeed, the authors of this study suggest that HLA-I may be a better marker than thiazole orange to determine the percentage of young platelets in patient samples.…”
Section: Surface Receptor Contentsupporting
confidence: 65%
“…Using temporal labelling in a murine model, our group demonstrated that as platelets age there is a significant reduction in GPVI. 41 Supporting this work, Veninga et al have recently shown that young platelets identified by HLA-I expression have higher GPVI levels than old platelets. 17 Conversely, following platelet depletion using an anti-GPIba antibody in mouse, the newly formed platelets had similar levels of surface GPVI, although with an impairment in the associated downstream signalling pathways.…”
Section: Surface Receptor Contentsupporting
confidence: 61%
See 3 more Smart Citations